A Modified Tumor-Node-Metastasis Classification for Stage III Colorectal Cancers Based on Treating Tumor Deposits as Positive Lymph Nodes - Pei, Jun-Peng; Zhang, Chun-Dong; Fu, Xiang; Ba, Yong; Yue, Shuai; Zhao, Zhe-Ming; Dai, Dong-Qiu (Frontiers in Medicine, 2020)
Background: The TNM classification of the AJCC classified tumor deposits (TDs) in patients with colorectal cancer (CRC) without lymph node (LN) metastasis as N1c, but the classification of TDs in patients with LN metastases remains controversial. This study investigated the probability of regarding TDs as positive LNs (pLNs) in pN stage and estimated its prognostic ability in CRC. Methods: We used the Surveillance, Epidemiology, and End Results program to analyze CRC patients who underwent surgical therapy (14,906 training cohort, 6,384 validation cohort). A modified pN stage (mpN) was identified using the number of pLNs plus TDs. Overall survival (OS) was analyzed using Kaplan–Meier survival curves and significant prognostic factors were identified by univariate and multivariate analyses. Prognostic ability was estimated using the area under the curve (AUC), calibration curve, and Akaike’s information criterion (AIC). Clinical benefit was measured by decision curve analyses (DCA). The results were validated using the validation cohort. Results: Both pN and mpN stages were independent prognostic factors in CRC according to univariate and multivariate analyses. AUC analysis showed mpN stage had better prognostic discrimination for OS than pN stage (0.612 vs. 0.605, P < 0.001). AIC demonstrated that mpN stage also showed superior model-fitting compared with pN stage (49,756 vs. 49,841). DCA further revealed that mpN stage had better clinical benefits than pN stage. The validation cohort showed similar findings. Conclusions: We concluded that counting TDs as pLNs may be superior to the pN stage when assessing the prognosis of CRC patients.